The Psychological Effect of COVID-19 on Home-Quarantined Nursing Students in China - Li, Dandan; Zou, Li; Zhang, Zeyu; Zhang, Pu; Zhang, Jun; Fu, Wenning; Mao, Jing; Cao, Shiyi (Frontiers in Psychiatry, 2021)
Coronavirus disease 2019 (COVID-19) has significantly caused socioeconomic impacts. However, little is known about the psychological effect of COVID-19 on home-quarantined nursing students. The present study aimed to identify the prevalence and major determinants of anxiety, depression and post-traumatic stress symptoms (PTSS) in Chinese nursing students during the COVID-19 pandemic quarantine period. An online survey was conducted on a sample of 6,348 home-quarantined nursing students. Mental health status was assessed by the Generalized Anxiety Disorder 7-Item Scale (GAD-7), the Patient Health Questionnaire 9-Item Scale (PHQ-9) and the Post Traumatic Stress Disorder Check List-Civilian version (PCL-C), respectively. Logistic regression analyses were performed to identify risk factors of anxiety, depression and PTSS. The overall prevalence of anxiety was 34.97%, and the rates of ‘mild’, ‘moderate’ and ‘severe’ anxiety were 26.24%, 7.04% and 1.69%, respectively. Depression was detected in 40.22% of the nursing students, and the prevalence of ‘mild’, ‘moderate’, ‘moderately severe’ and ‘severe’ depression was 27.87%, 7.18%, 4.08% and 1.09%, respectively. The overall prevalence of PTSS was 14.97%, with the prevalence of ‘mild’ and ‘moderate-to-severe’ PTSS reported at 7.04% and 7.93%, respectively. Male gender and insufficient social support were common risk factors for anxiety, depression and PTSS. In conclusion, about one-third, two-fifths and one-seventh of Chinese nursing students had anxiety, depression and PTSS during the period of home quarantine, respectively. Timely and appropriate psychological interventions for nursing students should be implemented to reduce the psychological harm caused by COVID-19 pandemic.